FROM “NON” TO “BREAD”: CULTURALLY RELEVANT ENGLISH FOR UZBEK LEARNER - Inoqova Sabina Xolmurod qizi; Eshmanova Shahrizoda Mamanazar qizi (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
Learning English at the beginner level can be a life-changing journey, especially for students in Uzbekistan where English is increasingly becoming a necessity in education, employment, and international communication.